KOMUNIKASI TERAPEUTIK DENGAN KEPUASAN PASIEN DALAM PELAYANAN PRIMA DI RUANG RAWAT INAP SERUNI RSUD TAMAN HUSADA BONTANG TAHUN 2023 - Ani Liyana; Rasmun Rasmun; Abd Kadir (Bajang Institute, 2023)
Therapeutic communication is one way to provide accurate information and foster a trusting relationship with clients so that clients will feel satisfied with the nursing services they receive. A nurse's good communication skills have a direct impact on patient satisfaction, that is, the feelings that arise as a result of the performance of health services obtained after being compared to what he expected. In this study, researchers wanted to know the relationship between nurses' therapeutic communication and the level of patient satisfaction in the inpatient room of Taman Husada Bontang Hospital. The samples in this study were patients in the inpatient room of Taman Husada Bontang Hospital, visitors to the South Sanggatta Health Center inpatient poly, totaling 59 people. In this study, the sampling technique used was Non-probobality sampling with Acidental Sampling technique. Accidental Sampling is a sampling technique based on chance, so that researchers can take samples from anyone they meet without prior planning. The results of the Chi Square statistical test in table 4.4 obtained a P-value value of < a where the P-value (0.004)<a (0.05) so that it can be concluded that there is a significant relationship between nurses' therapeutic communication and patient satisfaction in the seruni room of Taman Husada Bontang Hospital in 2023.